A panel of urinary proteins predicts active lupus nephritis and response to rituximab treatment. (12th December 2020) - Davies, Jennifer C; Carlsson, Emil; Midgley, Angela; Smith, Eve M D; Bruce, Ian N; Beresford, Michael W; Hedrich, Christian M; ,
Abstract: Objectives: ∼30% of patients with SLE develop LN. Presence and/or severity of LN are currently assessed by renal biopsy, but biomarkers in serum or urine samples may provide an avenue for non-invasive routine testing. We aimed to validate a urinary protein panel for its ability to predict active renal involvement in SLE. Methods: A total of 197 SLE patients and 48 healthy controls were recruited, and urine samples collected. Seventy-five of the SLE patients had active LN and 104 had no or inactive renal disease. Concentrations of lipocalin-like prostaglandin D synthase (LPGDS), transferrin, alpha-1-acid glycoprotein (AGP-1), ceruloplasmin, monocyte chemoattractant protein 1 (MCP-1) and soluble vascular cell adhesion molecule-1 (sVCAM-1) were quantified by MILLIPLEX ® Assays using the MAGPIX Luminex platform. Binary logistic regression was conducted to examine whether proteins levels associate with active renal involvement and/or response to rituximab treatment. Results: Urine levels of transferrin ( P  <0.005), AGP-1 ( P  <0.0001), MCP-1 ( P  <0.001) and sVCAM-1 ( P  <0.005) were significantly higher in SLE patients when compared with healthy controls. Furthermore, levels of transferrin, AGP-1, ceruloplasmin, MCP-1 and sVCAM-1 (all P  <0.0001) were higher in SLE patients with active LN when compared with patients without active LN. A combination of five urine proteins, namely LPGDS, transferrin, ceruloplasmin, MCP-1 and sVCAM-1 was a good predictor of active LN (AUC 0.898). A combined model of LPGDS, transferrin, AGP-1, ceruloplasmin, MCP-1 and sVCAM-1 predicted response to rituximab treatment at 12 months (AUC 0.818). Conclusions: Findings support the use of a urinary protein panel to identify active LN and potentially predict response to treatment with rituximab in adult SLE patients. Prospective studies are required to confirm findings.